Anti-quorum Sensing and Antimicrobial Effect of Mediterranean Plant Essential Oils Against Phytopathogenic Bacteria - Camele, Ippolito; Elshafie, Hazem S.; Caputo, Lucia; De Feo, Vincenzo (Frontiers in Microbiology, 2019)
Essential oils (EOs) are one of the most interesting natural products extracted from different aromatic plants. EOs have been considered for few centuries as an essential part of the traditional pharmacopeia. Many plant EOs have been reported as possible effective alternatives for commercial pesticides. The current mini review gives a general overview about microbicide effect as well as anti-quorum sensing and anti-biofilm formation of some common plant EOs especially from Lamiaceae and Verbanaceae families commonly grew in Mediterranean region against some serious food phytopathogenic bacteria.